(untitled) (Englisia : Journal of Language, Education, and Humanities, 2023)
Despite the growing interest in research on Teacher Professional Development (TPD) carried out by previous researchers, the voices of local EFL teachers in different regions in Indonesia in which top-down TPD activities are still prevalent remain underrepresented. As a result, in order to fill a gap in the literature, the current study sought to investigate the TPD activities undertaken by EFL teachers, the extent to which those formal TPD programs had an impact on their professional development based on their perceptions, and the constraints that they encountered. This descriptive qualitative study utilized a questionnaire and semi-structured interview as the instruments to gather the data and ensure triangulation for trustworthiness. Twenty-five English teachers from various Junior High schools associated with MGMP in Cirebon, West Java were voluntarily involved in this research. The result revealed that TPD activities that the participants have undertaken all these times helped them improve self-efficacy, attitudes, beliefs, reflective competence, classroom practice and instructional skills, and teacher knowledge and skills. Nevertheless, some challenges such as excessive workload as a teacher, time constraints or mismatched schedule, limited choices of TPD programs that were not in line with teachers’ interests, the mismatch between teachers’ needs and what the program offered, limited access and information about the programs, and less effective program duration remained prevalent during the TPD program implementation.